2019
DOI: 10.1002/acm2.12679
|View full text |Cite
|
Sign up to set email alerts
|

Three IMRT advanced planning tools: A multi‐institutional side‐by‐side comparison

Abstract: Purpose: To assess three advanced radiation therapy treatment planning tools on the intensity-modulated radiation therapy (IMRT) quality and consistency when compared to the clinically approved plans, referred as manual plans, which were planned without using any of these advanced planning tools.Materials and Methods: Three advanced radiation therapy treatment planning tools, including auto-planning, knowledge-based planning, and multiple criteria optimization, were assessed on 20 previously treated clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…However, no statistically significant difference was found among the three kinds of plans, indicating that the KBP method can produce comparable or even better plans than the traditional manual way. This observation was consistent with previously published studies ( 15 , 28 , 29 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, no statistically significant difference was found among the three kinds of plans, indicating that the KBP method can produce comparable or even better plans than the traditional manual way. This observation was consistent with previously published studies ( 15 , 28 , 29 ).…”
Section: Discussionsupporting
confidence: 94%
“…By introducing estimated DVHs, patient-specific optimization objectives rather than general templates were generated for each individual patient in the KBP method, based on the patient anatomy and prior knowledge. This helped offer a clearer directionality for the planner to refine the optimization objectives and achieve a high quality plan, which would be particularly useful for some complicated disease sites such as cancer of the head and neck ( 28 ). Our results showed that the EXP method provided the best trade-off between target dose coverage and normal tissue protection, acquiring the highest quality assessment scores among the three kinds of IMRT plans.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [ 23 ] by Lu et al compared plan quality for four sites using three different advanced planning tools including AP. They showed that AP could improve plan quality, but the statistical power was limited by the small sample size-five patients for each site.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on the auto‐planning without FDVH guidance has shown improved or similar plan quality in comparison with the plans generated manually or using other automation algorithms. 16 , 17 , 19 , 21 , 22 Nonetheless, the auto‐planning algorithm required users to set planning dose goals, thus introducing subjectivity. Based on the skills and preferences of the planners, the planning dose goals entered by planners might be too loose or too stringent.…”
Section: Discussionmentioning
confidence: 99%
“…The plan qualities produced from these automation methods were reported to be comparable. 19 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%